Melanoidin degradation and electric energy production from palm oil waste using immobilized laccase-producing bacteria - Palasai, Wasan; Rothjanawan, Kronsirinut; Kongthong, Alisa; Yodrach, Rachchanon; Thipraksa, Junjira; Chaijak, Pimprapa (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
Melanoidin is a high molecular weight pigment that is problematic in agricultural wastewaters like palm oil mill effluent (POME). This study presents a novel approach combining a laccase-producing bacterial consortium primarily Lactiplantibacillus plantarum, immobilized on hydrothermally modified granular activated carbon (GAC) for efficient melanoidin degradation and simultaneous electricity generation in a microbial fuel cell (MFC). The hydrothermal modification of GAC enhanced bacterial immobilization and electron transfer, contributing to improved biodegradation performance. Gas chromatography-mass spectrometry (GC-MS) analysis identified a number of key degradation metabolites including silanediol, dimethyl; (1-methylethyl)benzene; limonene; and butylated hydroxytoluene, confirming an effective melanoidin breakdown. The system achieved 81.36 ± 1.07% melanoidin removal with electrochemical characterization that showed a maximum current density of 61.50 ± 1.98 mA/m² and power density of 1.51 ± 0.10 mW/m². These findings demonstrated the synergistic effect of hydrothermally modified GAC and the selected bacterial consortium offering a sustainable and innovative strategy for treating melanoidin-rich wastewater while recovering bioenergy.